(untitled) (Journal of Computational Innovation and Analytics (JCIA), 2025)
Game-based learning has gained traction as an innovative educational initiative, particularly in fields requiring strategic decision-making and operational management. This study explores the effectiveness of a board game, Port Management Game, as a pedagogical tool for enhancing students’ understanding of seaport management concepts. The primary objective of this study is to examine how board games can facilitate experiential learning, thus improving knowledge retention and supporting the development of critical decision-making skills among higher education students studying seaport management. A quasi-experimental research design involving a control and an experimental group was employed. The experimental group participated in board game sessions integrated into their coursework, while the control group underwent traditional lecture-based instruction. Data were collected through pre-tests and post-tests to assess students’ learning outcomes. A split-plot ANOVA was conducted to determine the statistical significance of the differences in performance between the two groups. The findings revealed that students in the experimental group demonstrated a statistically significant improvement in their understanding of seaport management concepts compared to those in the control group. The results align with existing literature supporting the use of game-based learning as an effective pedagogical strategy in higher education. The significance of this study lies in its contribution to maritime education by validating the use of board games as an interactive learning medium and as a tool in enhancing students’ understanding of lessons. The study also highlights the potential of board games to bridge theoretical knowledge with practical application, preparing students for real-world challenges in the maritime industry. Furthermore, the research underscores the suitability of board games as a stepping stone toward apprenticeship training, as they provide a structured yet flexible environment for learning by doing.